Pengaruh Crm (Customer Relationship Management) Dan Kualitas Kerja Terhadap Omzet Penjualan Pada Pt Dok Dan Perkapalan Kodja Bahari (Persero) Cabang Banjarmasin - Aldamitha Fatimah (BIMA: Jurnal Bisnis dan Manajemen, 2022)
Indonesia is known as an archipelagic country, so that sea transportation is often used, but not many know that ships must always be in good condition and meet classification standards, therefore opening up opportunities for the marine sector of the shipbuilding industry where the customers are not the general public so that the best service and quality are needed from the company for customers through CRM (Customer Relationship Management) and Work Quality variables. This study aims to determine whether there is a significant effect between CRM and Work Quality simultaneously and partially on Sales Turnover. The method used is descriptive quantitative, primary and secondary data sources, independent variables (CRM and work quality) and dependent variable (sales turnover), data collection through questionnaires, interviews, and observations. Analysis with Multiple Linear Regression using SPSS software version 21. The results show that 1) CRM and Work Quality variables have a simultaneous effect on Sales Turnover with the Fcount value greater than Ftable, namely 25.694 > 3.09, 2) The CRM variable has a partially significant effect with a Tcount value greater than Ttable (5.114 > 1.66), while the Work Quality variable does not have a significant effect partially with a Tcount value smaller than Ttable (1.348 < 1.66) on Sales Turnover, 3) Among the CRM and Work Quality variables that have the most dominant influence on Sales Turnover is the CRM variable with a value of Rpartial2 of 0.212 or 21.2% at PT Dok and Perkapalan Kodja Bahari (Persero) Banjarmasin Branch.